En la planta baja de la torre de marfil: veinte años de trayectoria del Instituto Valentín de Foronda - Rivera, Antonio (Huarte de San Juan. Geografía e Historia, 2015)
The Instituto Valentín de Foronda was set up in 1994 with the aim of consolidate the relationship between the University and the city of Vitoria and since then has developed a high-level research activity (both specifically in the field of History and in the Social Sciences as well). Along with this the Instituto hosts a research group that developed research from social history to the history of the nation identity making and finally to the history of political violence in the Basque Country.
Keywords: Basque Country; historiography; contemporary history; social history; political violence; terrorism; nation bulding